Detection and identification of Begomovirus infecting Cucurbitaceae and Solanaceae in Yogyakarta, Indonesia - APRILIA SUFI SUBIASTUTI; SEDYO HARTONO; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Subiastuti AS, Hartono S, Daryono BS. 2019. Detection and Identification of Begomovirus infecting Cucurbitaceae and Solanaceae in Yogyakarta, Indonesia. Biodiversitas 20: 738-744. Begomovirus genome has high plasticity that led to evolve rapidly. Begomovirus is one of a remarkably successful group of emerging viruses as the results from combination of many factors. Planting systems in Indonesia which often overlapping two or more plant species in one land has high possibility for occurring mixed infection. It is also suggested has high contribution to increase Begomovirus diversity. The aim of this research is to do preliminary identification of Begomovirus infected-Solanaceae and Cucurbitaceae in Yogyakarta based core coat protein (CP) gene sequence. A total of 50 melon, 50 chili, 30 eggplants, and 30 watermelon samples which showed Begomovirus symptoms were observed from several fields in Yogyakarta and Purworejo, Indonesia during 2016. Almost 90% of infected samples for each plant were tested by PCR and showed positive for Begomovirus. Based on coat protein (CP) gene nucleotide sequence identity, Begomovirus infected Solanaceae in Indonesia has close relationship with Pepper yellow leaf curl Indonesia virus (PepYLCIV) and Tomato yellow leaf curl Kanchanaburi virus (TYLCVKaV), while in Cucurbitaceae has close relationship with Squash leaf curl China virus (SLCCV) Tomato leaf curl New Delhi virus (ToLCNDV). All collected isolates showed highest sequence identity with isolates from South-East Asia and China. However, further analysis that including full genome characterization is still needed to explain Begomovirus evolution in Indonesia.